Immersion in an emergency department triage center during the Covid-19 outbreak: first report of the Liège University hospital experience. Issue 1 (2nd January 2022) - Gilbert, Allison; Brasseur, Edmond; Petit, Mérédith; Donneau, Anne Françoise; Diep, AnhNguyet; Hetzel Campbell, Suzanne; Servotte, Jean-Christophe; Piazza, Justine; Ancion, Aurore; Gensburger, Mathieu; D'Orio, Vincent; Ghuysen, Alexandre
ABSTRACT: Objectives: Since the beginning of the novel coronavirus outbreak, different strategies have been explored to stem the spread of the disease and appropriately manage patient flow. Triage, an effective solution proposed in disaster medicine, also works well to manage Emergency Department (ED) flow. The aim of this study was to describe the role of an ED Triage Center for patients with suspected novel coronavirus disease (Covid-19) and characterize the patient flow. Methods: In March 2020, we established a Covid-19 triage center close to the Liège University EDs. From March 2 to March 23, we planned to analyze the specific flow of patients admitted to this triage zone and their characteristics in terms of inner specificities, work-up and management. During this period, all patients presented to the ED with symptoms suggestive of Covid-19 were included in the study. Results: A total amount of 1071 patients presented to the triage center during the study period. 41.50% of the patients presented with flu-like symptoms. In 82.00% of the cases, no risk factor of virus transmission was found. The SARS-Cov2 positive patients represented 29.26% of the screened patients. 83.00% of patients were discharged home while 17.00% were admitted to the hospital. Conclusion: Our experience suggests that triage centers for the assessment and management of Covid-19 suspected patients is an essential key strategy to prevent the spread of the disease among non-symptomatic patients who present to the EDs for care. This allows for a disease-centered work-up and safer diversion of Covid-19 patients to specific hospital units.